2023
DOI: 10.1002/psp.2708
|View full text |Cite
|
Sign up to set email alerts
|

The role of non‐resident family ties in rural staying

Sara Ferguson,
Tialda Haartsen,
Annett Steinführer
et al.

Abstract: Internal migration research is paying increasing attention to the role in migration behaviour of having non‐resident family—family living outside of the household—living close by, and also to non‐migration and staying in general. Combining these two themes, this paper investigates the role of non‐resident family ties in rural staying for adults aged 31–64. Using a mixed methods analysis of survey and interview data from the Netherlands, Germany and Northern Ireland (UK), we examine if the presence of non‐resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Stockdale and Ferguson (2020) similarly found "that attachment and belonging to the home place is entangled in complex patterns of family history, farm ownership and continuing familial networks" (p. 369). A sense of belonging has previously been found to contribute to the expectation to stay in rural areas (Hofstede et al, 2022), and has been reported as a motive for staying (Ferguson et al, 2023;Stockdale & Ferguson, 2020;Stockdale, Theunissen, et al, 2018) and returning (von Reichert et al, 2014). It seems especially likely that a shared place of origin with (grand)parents increases one's propensity to stay or return.…”
Section: Longstanding Residential Histories As Multigenerational Loca...mentioning
confidence: 97%
See 2 more Smart Citations
“…Stockdale and Ferguson (2020) similarly found "that attachment and belonging to the home place is entangled in complex patterns of family history, farm ownership and continuing familial networks" (p. 369). A sense of belonging has previously been found to contribute to the expectation to stay in rural areas (Hofstede et al, 2022), and has been reported as a motive for staying (Ferguson et al, 2023;Stockdale & Ferguson, 2020;Stockdale, Theunissen, et al, 2018) and returning (von Reichert et al, 2014). It seems especially likely that a shared place of origin with (grand)parents increases one's propensity to stay or return.…”
Section: Longstanding Residential Histories As Multigenerational Loca...mentioning
confidence: 97%
“…Geographic distances between adult children and parents are generally larger in countries with universal welfare models than in countries with family-based welfare models (Bordone, 2009;Hank, 2007). Nevertheless, ties to nearby, nonresident family members are found to constrain migration (Bjarnason & Haartsen, 2023) and contribute to intentions to remain immobile, also in countries with universal welfare models (Ferguson et al, 2023).…”
Section: Living Close To (Grand)parents As Multigenerational Local Tiesmentioning
confidence: 98%
See 1 more Smart Citation
“…‘The Role of Nonresident Family Ties in Rural Staying’ by Ferguson et al (2023—this issue) adopts a mixed‐method approach to explore how family networks in Germany, the Netherlands, and the United Kingdom influence individuals' desires and decisions to remain in place. Their study brings further nuance to the discussion of rural staying and emphasises how family solidarity and a sense of belonging and identity promote immobility, particularly in rural contexts.…”
Section: The Contributions To This Special Issuementioning
confidence: 99%